Gemmatirosa adaptations to arid and low soil organic carbon conditions worldwide - Yuanyuan Bao; Tadeo Sáez-Sandino; Youzhi Feng; Xuebin Yan; Shiying He; Shilun Feng; Ruirui Chen; Hui Guo; Manuel Delgado-Baquerizo (Geoderma)
Aridity and warming accelerate soil organic carbon (SOC) loss, thereby compromising essential functions of soil health, such as nutrient retention and microbial diversity. However, the mechanisms by which microbes adapt to arid and low SOC conditions remain poorly understood. Here, using data from an 8-y field-scale manipulation experiment, we found that the largely undescribed Gemmatimonadetes could be among the well-adapted bacterial taxa for thriving under low SOC content and arid ecosystems. Their enhanced ability to tolerate drought stress—mediated by metabolic pathways for the synthesis of osmolytes (e.g., glycine, betaine, choline, ectoine, and histidine)—and their capacity to acquire carbon resource through glycoside hydrolase genes involved in organic matter decomposition (41.6 % and 11.8 % higher than those in the total bacterial community, respectively), could explain this pattern. Further analyses based on a global-scale standardized field survey covering all continents and major ecosystem types further confirmed that Gemmatimonadetes—and, at a finer resolution, Gemmatirosa—predominated in arid (with a peak relative abundance of Gemmatimonadetes reaching 3.8 % in dry grasslands) and warm regions (peaking at 4.5 % in Africa) of the planet, where the SOC content is low. Our work provides new insights into how a largely neglected microbial group, such as Gemmatimonadetes/Gemmatirosa, can adapt to increasing environmental stress in arid and low-carbon environments in a changing world.